Matthys Gerber - Messham-Muir, Kit (ARTFORUM, 2016)
Dutch-born Australian painter Matthys Gerber has been a fixture of the notoriously quarrelsome Sydney contemporary art scene for roughly three decades. Consistently provocative and protean in terms of style and content, his work has been routinely dismissed by conservative commentators as cynical dilettantism or careerist one-upmanship. For Gerber’s first major survey, Museum of Contemporary Art Australia senior curator Natasha Bullock countered this perception by framing the artist’s output as a metacritique of painting in the Australian context, claiming that his work “has always carved a singular path through the ‘idea’ of painting.” The thirty-five works presented here as an evenly representative, if not comprehensive, jumble of distinct phases portrayed an artist constantly probing the limits and conditions of his own subjectivity and practice.